2014
DOI: 10.1038/ng.3002
|View full text |Cite|
|
Sign up to set email alerts
|

Rare variants of large effect in BRCA2 and CHEK2 affect risk of lung cancer

Abstract: We conducted imputation to the 1000 Genomes Project of four genome-wide association studies of lung cancer in populations of European ancestry (11,348 cases and 15,861 controls) and genotyped an additional 10,246 cases and 38,295 controls for follow-up. We identified large-effect genome-wide associations for squamous lung cancer with the rare variants of BRCA2-K3326X (rs11571833; odds ratio [OR]=2.47, P=4.74×10−20) and of CHEK2-I157T (rs17879961; OR=0.38 P=1.27×10−13). We also showed an association between com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
337
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 403 publications
(367 citation statements)
references
References 65 publications
12
337
3
2
Order By: Relevance
“…The estimated FRRs of the most common adult cancers were restricted to a narrow range of 1.4 to 1.6, which are lower than those previously observed in family-based studies (1,5,6). A number of additional factors are likely to contribute to familial aggregation, including rare genetic variants (23)(24)(25), nonadditive effects, and shared environment. Expanding GWAS, either through new genotyping or metaanalyses, should continue to yield new susceptibility loci.…”
Section: Discussionmentioning
confidence: 57%
“…The estimated FRRs of the most common adult cancers were restricted to a narrow range of 1.4 to 1.6, which are lower than those previously observed in family-based studies (1,5,6). A number of additional factors are likely to contribute to familial aggregation, including rare genetic variants (23)(24)(25), nonadditive effects, and shared environment. Expanding GWAS, either through new genotyping or metaanalyses, should continue to yield new susceptibility loci.…”
Section: Discussionmentioning
confidence: 57%
“…Genetic heritability of lung cancer is estimated to be 14% (1), but only a few genetic risk loci have been identified to date in genome-wide association studies (GWAS) of lung cancer in Europeans (2). Epidemiological studies have shown associations between lung cancer and cardiovascular disease (CVD) risk factors related to the metabolic syndrome (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…DNA damage can cause CHEK2 phosphorylation (15), activated CHEK2 can lead to phosphorylation of the CDC25 family, BRCA1, p53, and other similar functional effectors in order to start the cell cycle checkpoint regulation (15)(16)(17). Results from previous studies have shown a relationship between the CHEK2 mutation and an increased risk for lung cancer (18,19), breast cancer (20,21), prostate cancer (22,23), colorectal cancer (24,25) and other cancers (26,27). In addition, there was a relationship between the decreased risk of endometrial cancer and the rs8135424 CHEK2 SNP (28).…”
Section: Introductionmentioning
confidence: 99%